Identification of novel fusion transcripts in multiple myeloma. Issue 8 (16th February 2018) - Lin, Mingxuan; Lee, Peak Ling; Chiu, Lily; Chua, Constance; Ban, Kenneth H K; Lin, Adeline H F; Chan, Zit Liang; Chung, Tae-Hoon; Yan, Benedict; Chng, Wee-Joo
Abstract : Aims: Multiple myeloma (MM) is a heterogeneous disease characterised by genetically complex abnormalities. The classical mutational spectrum includes recurrent chromosomal aberrations and gene-level mutations. Recurrent translocations involving the IGH gene such as t(11;14), t(4;14) and t(14;16) are well known. However, the presence of complex genetic abnormalities raises the possibility that fusions other than the recurrent IGH translocations exist. We therefore employed a targeted RNA-sequencing panel to identify novel putative fusions in a local cohort of MM. Methods: Targeted RNA-sequencing was performed on 21 patient samples using the Illumina TruSight RNA Pan-Cancer Panel (comprising 1385 genes). Fusion calls were generated from the Illumina RNA-Sequencing Alignment software (V.1.0.0). These samples had conventional cytogenetic and fluorescence in situ hybridisation data for the common recurrent chromosomal abnormalities (t(11;14), t(4;14), t(14;16) and 17p13 deletion). The MMRF CoMMpass dataset was analysed using the TopHat-fusion pipeline. Results: A total of 10 novel fusions were identified by the TruSight RNA Pan-Cancer Panel. Two of these fusions, HGF / CACNA2D1 and SMC3 / MXI1, were validated by reverse transcription PCR and Sanger sequencing as they involve genes that may have biological relevance in MM genesis. Four of these ( MAP2K4 / MAP2K4P1 ) are likely to be spurious secondary to misalignment of reads to a pseudogene. One record of the HGF/CACNA2D1 fusion was identified from the MMRF CoMMpass dataset. Conclusions: The identification of novel fusions offers insights into the biology of MM and might have clinical relevance. Further functional studies are required to determine the biological and clinical relevance of these novel fusions.